Sistem Kontrol dan Monitoring Daya Output Hybrid PLTS dan PLTB - Nazib, Ainun; Mardianto, Eko; Rianda (entries, 2025)
The current energy crisis encourages the use of renewable energy resources to reduce dependence on non-renewable fossil fuels. The use of renewable energy resources is environmentally friendly, especially in power generation. The research method uses a Hybrid PLTS and PLTB output power control and monitoring system, which monitors both solar power plants and windmills. Data from the sensor is stored according to the time of collection, and monitored via a Smartphone or Laptop device using the ThinkSpeak website via the ESP32 microcontroller. The sensors used include the Non-Inverting Buffer Sensor and the ACS758 Sensor. Temperature, temperature and wind testing is carried out with a DHT22 sensor and an anemometer. DHT and Annemometer sensor data do not use a data storage system, only monitoring.